AUTOMATIC COUNTING OF COLONY FORMING UNITS IN SAMPLES OF TENDERLOIN USING OPENCV LIBRARY - Zonta, A.; Luz, P. A. C.; Andrigheto, C.; Zonta, M. C. M. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Meat is a good medium for the multiplication of microorganisms and can be contaminated during raw material acquisition, processing, storage, transport or preparation. Routinely hundreds of petri dishes are used for inspection of food products in laboratories where trained technicians perform counting of the colony forming units on these plates. Like any repetitive task, this analysis is susceptible to human failures and requires a reasonable amount of time. The objective of this work was to develop a simple algorithm that does not depend on controlled lighting, to perform the automatic counting of colony forming units in samples of tenderloin. The algorithm was developed using the Python v2.7 programming language and the OpenCV v3.0 image processing library. The average error in automatic counting was 7.7% for the 40 plates processed. No significant contaminations were found in the analyzed bovine cuts. The average time used in the counting by the visual and automatic method was 44.6 and 2.07 seconds, respectively. The developed system presented promising initial results. Non homogeneous illumination, irregular shape and contact between colonies have a strong impact on the results.